IMPLEMENTATION OF DIVERSION IN HANDLING CRIMINAL CASES VIOLENCE AGAINST CHILDREN IN CONFLICT WITH THE LAW - Ridawati, Nur Haji (Jurnal Hukum Khaira Ummah, 2024)
The purpose of this study is to examine and analyze the implementation of diversion and its obstacles in handling cases of criminal acts of violence against children in conflict with the law. In this writing, the author uses the Sociological juridical method or an approach with direct surveys in the field and secondary data through library studies with research specifications in the form of descriptive analysis. One of the efforts to analyze and explain legal problems related to objects with a comprehensive and systematic description of everything related to the diversion of children in conflict with the law. protection of children in conflict with the law, namely through Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The existence of the Law on the Criminal Justice System in its implementation there is a requirement to uphold justice for children in conflict with the law, namely by implementing restorative justice as one method of resolving child cases in Indonesia. The purpose of such juvenile justice is operationally played by law enforcement officers, in this context to law enforcement officers as regulated in Law No. 2 of 2002 concerning the Indonesian National Police is given the widest possible freedom and in all examination improvements to exercise discretion. The implementation of diversion is motivated by the desire to avoid negative effects on the soul and development of children by their involvement with the criminal justice system. The implementation of diversion by law enforcement officers is based on the authority of law enforcement officers called discretion; is the authority of law enforcement officers who handle criminal cases.